Phylogeographic structure of Brachymystax lenok tsinlingensis (Salmonidae) populations in the Qinling Mountains, Shaanxi, based on mtDNA control region. (August 2015) - Liu, Haixia; Li, Yang; Liu, Xiaolin; Xiong, Dongmei; Wang, Lixin; Zou, Guiwei; Wei, Qiwei
Abstract Brachymystax lenok tsinlingensis is an endangered freshwater fish and distributed in mountains steams of Qinling Mountains, China. In this study, a comparative study of the mtDNA control region (D-loop) was performed to analyze its natural population structure and the genetic diversity of 53 individuals from four locations (TB, YX, LX and ZZ populations). Sequence analysis revealed three different domains and two feature sequences of the control region. The estimated haplotype and nucleotide diversity were 9 and 0.0023, respectively. Genetic structure analysis showed a high-level genetic diversity of B. lenok tisnlingensis (h = 0.6060 ± 0.1499). The AMOVA analysis indicated that 26.02% of total variation came from individual populations, and 73.98% from variation within the four geographic populations, which showed low genetic differentiation between the four geographic groups. Test of neutral evolution and mismatch distribution indicated that no historical expansion occurred in these populations. The high genetic diversity and low genetic differentiation would provide new information for conservation and exploitation of this species.